Using an integrated teaching and learning approach to deliver inter-professional practice in Public Health. (October 2015) - Senior, Emma; Telford, Mark
Summary: In order to address health inequalities an interprofessional approach is required. To recreate this experience for pre-registration healthcare students an innovative model utilising integrated approaches to teaching and learning was developed. This incorporated interprofessional education, threshold concepts, virtual learning and narrative pedagogy. Highlights: Producing a stimulating approach for students to learn Adopting an integrated methodology to promote interprofessional education Delivering an intellectually inspiring student experience